2019
DOI: 10.3389/fnins.2019.01336
|View full text |Cite
|
Sign up to set email alerts
|

Performance Monitoring via Functional Near Infrared Spectroscopy for Virtual Reality Based Basic Life Support Training

Abstract: Keywords: functional near infrared spectroscopy, basic life support, medical training, virtual reality, medical simulator Frontiers in Neuroscience | www.frontiersin.org December 2019 | Volume 13 | Article 1336Conflict of Interest: fNIR Devices, LLC manufacturers the optical brain imaging instrument and licensed IP and know-how from Drexel University. KI and BO were involved in the technology development and thus offered a minor share in the startup firm, fNIR Devices, LLC.The remaining authors declare that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…In this regard, our study results are consistent with those of studies proposing that complex education systems that integrate didactic learning models and distance education systems positively influence learning [22,23]. One of the most critical distance education problems is feedback and testing of lesson elements [7,24]. Assessments of the performance were mostly made with traditional methods in many studies comparing e-education models and traditional education models.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this regard, our study results are consistent with those of studies proposing that complex education systems that integrate didactic learning models and distance education systems positively influence learning [22,23]. One of the most critical distance education problems is feedback and testing of lesson elements [7,24]. Assessments of the performance were mostly made with traditional methods in many studies comparing e-education models and traditional education models.…”
Section: Discussionsupporting
confidence: 89%
“…The coronavirus disease 2019 (COVID-19) pandemic has necessitated the switch to distance education through abandoning face-to-face education worldwide [1][2]. Distance education models have been used in medical education during the recent 30 years; distance practical education is still a problem [3][4][5][6][7]. On the other hand, useful and reliable methods could not be developed to evaluate distance education efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…Aksoy et al divided subjects into four groups, based on virtual reality experience and basic life support knowledge (Basic Life Support (BLS)). Their study confirmed that BLS training scores relate to the fNIRS parameters of the prefrontal cortex region [ 37 ]. Teo et al took 26 healthy older adults, 23 older adults with memory impairment, and 9 older adults with dementia as subjects and proved that the dual-task gait can be used for memory impairment, but compared to healthy people, O2Hb increased significantly, while those with dementia decreased significantly [ 39 ].…”
Section: Discussionmentioning
confidence: 56%
“…Although our study does not directly verify the detailed physiological mechanism of cognitive function regulation when subjects undergo GBIT, many studies in the past have confirmed the relationship between serious games and brain blood flow and metabolism [ 37 40 ]. Katzorke et al recruited 55 older adults with dementia and 55 healthy older adults as subjects and used a verbal fluency task to compare the difference in brain hemodynamics between dementia and healthy people.…”
Section: Discussionmentioning
confidence: 74%
“…Hemodynamic responses in the prefrontal cortex (PFC) region of the brain elicited by different stimuli can be monitored with these optical systems [ 14 , 15 , 16 , 17 ]. Further, fNIRS has been used as an assessment tool in medical simulation training in addition to the current scoring systems [ 18 , 19 ]. The objective of this study was to investigate whether neurophysiological measures of trainees could be used as an additional monitoring tool for assessing the training effect of robotic surgery simulators.…”
Section: Introductionmentioning
confidence: 99%